2015
DOI: 10.2399/yod.15.008
|View full text |Cite
|
Sign up to set email alerts
|

University Choice Process: A Literature Review on Models and Factors Affecting the Process

Abstract: I In recent years, the environment of higher education has dramatically changed. For a long time, higher education was regarded as a luxury rather than a necessity (Gonchar, 1995;Tansel and Bircan, 2006). Many people even considered higher education as an elitist activity. Over the course of time, as people clearly observed the importance of higher education, the demand for it increased exponentially. To meet an increasing social demand for higher education, the inabilities of state universities have led to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 49 publications
0
19
1
Order By: Relevance
“…This means that the better or worse a person's personality will not affect their interests. However, the results of this study contradict with other studies (Haryanti et al, 2016;Proboyo & Soedarsono, 2015;Tamtekin Aydın, 2015). Then, Nurfia (2018) found that the factors affecting student choosing Office Administration Education Study Program is a factor family, friendship, individual personality, school, image campus and employment prospects.…”
Section: Result Discussion and Suggestionscontrasting
confidence: 85%
“…This means that the better or worse a person's personality will not affect their interests. However, the results of this study contradict with other studies (Haryanti et al, 2016;Proboyo & Soedarsono, 2015;Tamtekin Aydın, 2015). Then, Nurfia (2018) found that the factors affecting student choosing Office Administration Education Study Program is a factor family, friendship, individual personality, school, image campus and employment prospects.…”
Section: Result Discussion and Suggestionscontrasting
confidence: 85%
“…Most of these studies either focus on domestic vs. foreign or are related just to the students' choice without mentioning AACSB or any other international accreditation. Tamtekin Aydın [26] published a literature review on the university choice process and among the main factors, family, reference groups, reputation, location, job prospects, personal factors, and financial factors such as cost or financial aid were identified. Nemar and Vrontis [27] conducted a similar analysis focusing on Lebanon but their goal was to research the students' choice in order to help universities to segment their customers and to better target their marketing efforts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many studies have shown that university student choice decisions are influenced by university attributes. These attributes are identified as quality of staff, type of institution, availability of desired programs, curriculum, international reputation, quality of facilities such as libraries, computerized and social facilities, campus and class sizes and availability of financial assistance (Aydin, 2015).…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…Shanka et al (2005) explain that family influence is a major factor in the choice of higher education. Because almost all students consult with their parents about their higher education plans (Aydin, 2015). Aguado et al (2015) explained parents are the financiers of the education of their children, they have a significant influence on their children choosing higher education (Rudhumbu, 2017).…”
Section: The Effect Of Parental Support On the Decision To Choose School Of Acupuncturementioning
confidence: 99%
See 1 more Smart Citation